Faktor Penentu Donor untuk Berwakaf: Sebuah Eksplorasi Wakaf dalam Literatur - Gustina; Vera Pujani; Yulia Hendri Yeni; Mohamad Fany Alfarisy (Department of Islamic Economics, IPB University, 2021)
The purpose of this study was to determine the factors that influence donors in giving waqf. In addition, it also gives consideration to decision makers related to waqf in Indonesia. The method in this study is a qualitative research with a description of previous research, through secondary data obtained from scientific journals, websites, books, and other electronic media sources related to the study discussed. The journals reviewed are journals published from 2012-2021. The theories discussed in this study are TRA and TPB. The findings of this study indicate that the factors of religiosity, attitude, subject norm, and convenience have a significant positive effect on the amount of waqf issued by donors or waqif (waqf givers). Through this study, it is hoped that this will become a consideration, especially for writers, as well as readers, and recommendations for waqf institutions to increase the convenience of the waqf system. In addition, the government (as a policy maker) should support waqf givers to continue to participate in this waqf practice for the good and welfare of the ummah.